Early Aging in Chernobyl Clean-Up Workers: Long-Term Study. (27th January 2015) - Krasnov, V.; Kryukov, V.; Samedova, E.; Emelianova, I.; Ryzhova, I.
Abstract : This paper represents data of long-term open prospective study. 312 male clean-up workers, who participated in elimination of the Chernobyl disaster consequences in 1986-87, were observed and examined in Moscow Research Institute of Psychiatry. The average age of patients was 57, 0 ± 6, 8 years. All patients were diagnosed with psychoorganic syndrome, caused by combination of different factors, which led to early cerebrovascular pathology, which was confirmed by clinical, neuropsychological, and instrumental examination. Anamnesis and the level of social adaptation were also assayed. Clinical estimation was done with the use of specially developed Clinical Psychopathological Chart. All the symptoms were divided into 4 groups (asthenic, psychovegetative, dysthymic, and cognitive symptom-complexes). No pronounced signs of dementia were observed. The control group included 44 clean-up workers without mental disorders. Predomination of various exogenous factors before and after accident was noted. Therapy included different vasotropic remedies, as well as family therapy, art therapy, and cognitive training. The possibilities of the reverse development of symptoms were statistically proved. The results allow making a conclusion that these disorders could not be explained either by radiation effects or by PTSD but connected with cerebrovascular pathology.